Aggregation‐Induced Emission Active Probe for Light‐Up Detection of Anionic Surfactants and Wash‐Free Bacterial Imaging. Issue 15 (17th February 2016) - Gao, Meng; Wang, Luochao; Chen, Junjian; Li, Shiwu; Lu, Guanhai; Wang, Lin; Wang, Yingjun; Ren, Li; Qin, Anjun; Tang, Ben Zhong
Abstract: Anionic surfactants are widely used in daily life and industries, but their residues can cause serious damage to the environment. The current detection methods for anionic surfactants suffer from various limitations and a new detection strategy is highly desirable. Based on 2‐(2‐hydroxyphenyl)benzothiazole fluorogen with aggregation‐induced emission characteristics, we have developed a fluorescent probe HBT‐C18 for selective and sensitive detection of anionic surfactants. By in situ formation of catanionic aggregates or micelles with anionic surfactants, the emission intensity of the HBT‐C18 probe can increase with increasing keto/enol emission ratio through restriction of intramolecular motion and excited‐state intramolecular proton‐transfer mechanisms. The probe can also be used for wash‐free imaging of bacteria enveloped by a negatively charged outer membrane. The results of this study provide a new strategy for sensitive detection of anionic surfactants and wash‐free bacterial imaging. Abstract : Based on 2‐(2‐hydroxyphenyl)benzothiazole fluorogen with aggregation‐induced emission (AIE) characteristics, a fluorescent light‐up probe HBT‐C18 has been developed for selective and sensitive detection of anionic surfactants by in situ formation of catanionic aggregates. The AIE‐active probe can also be used for monitoring catanionic micelle formation process and wash‐free bacterial imaging.